Analisis Ornamen (Gerga) Tradisional Karo pada Bangunan Kantor Bupati Karo Kabupaten Karo - Alit Dinda Mustika; Fuad Erdansyah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study aims to determine the extent of the application of traditional Karo ornaments which include the application, shape changes, and color changes in the Karo Regent Office building in Karo Regency. The population in this study were all ornaments found in the Karo Regent Office Building (total sampling) of 14 types of ornaments. This study uses a descriptive qualitative analysis approach based on the study of symbolic and Karo cultural philosophies. The results explained that the shape, color, and placement of the gerga no longer follow the rules based on the traditional placement of Karo. In Karo culture, gerga occupy structured fields in the traditional Karo house starting from the bottom (profane), middle (semi-sacred), and the top (sacred). In the upper part of the Karo Regent Office Building (Ayo-Ayo) the placement of the Gerga is in accordance with the Karo Traditional rules but not in the Derpih (wall) and Melmelen (kitchen bar) sections as well as the shape (proportion) changes and inconsistent color placement. . The conclusion of this study is that the ornaments that exist in the Karo Regent Office Building are used as decoration and aesthetic needs (profane) as a cultural identity of Karo, with the finding of a discrepancy in the placement of Karo ornaments based on the principle of ornamentation in the traditional Karo house. It is recommended that the placement, shape and color follow the ornamental principles found in the Karo traditional house.